ANALISIS PENGEMBANGAN KUALITAS PRODUK KANTONG SEMEN JENIS PASTED KRAFT DENGAN PENDEKATAN SIX SIGMA DI PT. XYZ: ANALISIS PENGEMBANGAN KUALITAS PRODUK KANTONG SEMEN JENIS PASTED KRAFT DENGAN PENDEKATAN SIX SIGMA DI PT. XYZ - Kharis Mandha Imawan; Andhika Mayasari; Sumarsono (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
The quality development is the most important thing that every company must do to minimize the defective products. One of the methods that can be used to analyze the defective products is Six Sigma which means as a method that can achieve, maintain, and maximize the success of business in a comprehensive and flexible way. The steps to be formulated by implementing the Six Sigma management cycle are DMAIC (Define, Measure, Analyze, Improve and Control). PT. XYZ which is engaged in manufacturing cement bags with one of its products is pasted kraft bags. The purpose of this study was to calculate the sigma score of the current conditions in the company, to analyze the causes of defective product that exceed the company's tolerance standards. The results showed three defective products. Those are printing defects, wrinkled bags and cutting defects. The average sigma score in the production process of Pasted kraft bags was 4.03 sigma, which means that out of 1 million products, there were around 5,858 defective products. The analysis of the core causes of product defects are the poor control of machine component conditions, the less attention of operators to standardize the machine settings, and the worn machine components during the production process. The repair step which is based on the 5W + 1H method are the recommendations for making a form to control the condition of engine components and good SOPs (Standard Operating Procedure), the procurement of field supervisors and regular training to operators.